2001
DOI: 10.1039/b105513p
|View full text |Cite
|
Sign up to set email alerts
|

A p-tert-butylcalix[4]arene functionalised at its lower rim with ether-amide pendant arms acts as an inorganic–organic receptor: structural and photophysical properties of its lanthanide complexes

Abstract: The new narrow-rim functionalised receptor 5,11,17,23-tetra-tert-butyl-25,26,27,28-tetrakis[2-(diethylcarbamoylmethoxy) III is 9-co-ordinated, being bound to the four ether and four carbonyl functions and to a water molecule itself H-bonded to the phenolic ether functions, which rigidifies the cavity formed by the pendant arms. Additionally, an ether molecule is inserted into the hydrophobic cavity defined by the aromatic rings. Both NMR (La, Lu) and luminescence (Eu, Tb) data point to a fairly high local symm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
32
0

Year Published

2002
2002
2021
2021

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 43 publications
(32 citation statements)
references
References 36 publications
0
32
0
Order By: Relevance
“…4 indeed showed the compound adopting a cone conformation in solution, in which the four complexing arms are held together in closed proximity, thereby providing a suitable octadentate coordination site for lanthanide cations. [14] The X-ray crystal structure of the lutetium complex further showed that a water molecule was encapsulated in the cavity formed by the four dioxo-ethylene bridges (OϪC1ϪC2ϪO), with H-bonding interactions between this water molecule and the oxygen atoms. Interestingly, an elemental analysis of free A 4 bL 4 revealed the presence of one water molecule, even after the drying process.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…4 indeed showed the compound adopting a cone conformation in solution, in which the four complexing arms are held together in closed proximity, thereby providing a suitable octadentate coordination site for lanthanide cations. [14] The X-ray crystal structure of the lutetium complex further showed that a water molecule was encapsulated in the cavity formed by the four dioxo-ethylene bridges (OϪC1ϪC2ϪO), with H-bonding interactions between this water molecule and the oxygen atoms. Interestingly, an elemental analysis of free A 4 bL 4 revealed the presence of one water molecule, even after the drying process.…”
Section: Resultsmentioning
confidence: 99%
“…Synthesis and Characterization of the Substituted Calixarene A 6 L 6 The branched calix [6]arene A 6 L 6 (Scheme 1) was obtained in two steps via a Williamson reaction (Scheme 2) from the brominated pendant arm ABr, synthesised as described previously, [14] and the calix [6]arene H 6 L 6 . The hexasodium derivative of calix [6]arene was prepared in toluene, demonstrating that this salt can be formed in a non-polar solvent despite the high fluxionality of calix [6] ) indicates complete functionalization of the phenoxide groups.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, the coordination cavity for the Ln() ion is tightened by a water molecule hydrogen bonded to the phenolic oxygen atoms and rigidifying it, so that the calixarene behaves as a good sensitiser of the Tb() luminescence. 11 Replacing the ether-amide substituents by dimethylphosphinoylmethylene pendant arms leads to B 4 bL 4 (Scheme 1), which interacts more strongly with Ln() ions, forming both 1 : 1 and 1 : 2 complexes in acetonitrile; in this case, solvent composition strongly influences the solvation state of the macrocyclic edifices. molecular mechanics and molecular dynamics calculations.…”
mentioning
confidence: 99%
“…With respect to the latter, our research program has focused on calixarenes bearing either ether amide 11 or phosphinoyl 12 groups. In previous papers we have reported on the interaction between A 4 bL 4 , a p-tert-butylcalix [4]arene substituted at the narrow rim with ether-amide pendant arms (Scheme 1).…”
mentioning
confidence: 99%